2012
DOI: 10.3390/ijms14010575
|View full text |Cite
|
Sign up to set email alerts
|

Why Flavins Are not Competitors of Chlorophyll in the Evolution of Biological Converters of Solar Energy

Abstract: Excited flavin molecules can photocatalyze reactions, leading to the accumulation of free energy in the products, and the data accumulated through biochemical experiments and by modeling prebiological processes suggest that flavins were available in the earliest stages of evolution. Furthermore, model experiments have shown that abiogenic flavin conjugated with a polyamino acid matrix, a pigment that photocatalyzes the phosphorylation of ADP to form ATP, could have been present in the prebiotic environment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…But in photolyases and fatty acid decarboxylases, rather than performing any methyl-group chemistry or redox chemistry, the large absorption cross section for visible light of both of these is instead exploited. They function as an antenna pigment, absorbing photons that would not be absorbed by FAD, and transferring this energy into the FAD and exciting it 113,115 . Once excited, FAD then transfers an electron to the substrate and reduces it, transiently becoming a radical stabilized by the apoprotein and a very strong oxidizing agent [113][114][115] .…”
Section: Ecological Interference Evolutionary Priority Effects and mentioning
confidence: 99%
See 1 more Smart Citation
“…But in photolyases and fatty acid decarboxylases, rather than performing any methyl-group chemistry or redox chemistry, the large absorption cross section for visible light of both of these is instead exploited. They function as an antenna pigment, absorbing photons that would not be absorbed by FAD, and transferring this energy into the FAD and exciting it 113,115 . Once excited, FAD then transfers an electron to the substrate and reduces it, transiently becoming a radical stabilized by the apoprotein and a very strong oxidizing agent [113][114][115] .…”
Section: Ecological Interference Evolutionary Priority Effects and mentioning
confidence: 99%
“…Thus, photolyases and fatty acid photodecarboxylases contain repurposed ordinary metabolic and redox cofactors which happen to be photoactive independent of their primary functions. to be on Earth 115,116 . It is not difficult to imagine how these light-transducing systems could become more optimized over evolutionary time, with customization of FAD and MTHF into dedicated phototrophic pigments and their electron flow being directed into electron transport chains and redox metabolism for carbon fixation.…”
Section: Ecological Interference Evolutionary Priority Effects and mentioning
confidence: 99%
“…On the basis of these insights, the effects of photon absorption by LOV photosensors can be dissected into a sequence of processes (see also Möglich et al ): The incoming signal, absorbed light, initiates a chemical reaction during which a metastable covalent adduct is formed between a flavin cofactor (carbon atom 4a) and a conserved cysteine residue of the LOV domain. The reaction proceeds via excitation of FMN with blue light (maximal energy of 266 kJ mol –1 for photons of 450 nm wavelength) to a singlet state, FMN*, that rapidly interconverts to a triplet state, 3 FMN, which then reacts with the sulfur of a neighbored cysteine side chain, resulting in the “light state” of the protein. , This protein state having a covalent cofactor adduct at its core differs from the “dark state” with respect to steric and electronic properties (strain, degrees of freedom, intramolecular interactions) and, consequently, induces a series of eventually small structural alterations that influence both local and global environment. Rearrangements of protein structure can furthermore be accompanied by altered protein dynamics .…”
Section: How Did Nature Design “Photocontrol Of Enzyme Function?”mentioning
confidence: 99%
“…Several biologists [100,101,102,103,104] have proposed that the primitive photosynthetic reaction centers were porphyrin—FeS couples (PSI type) or quinone types [95]. Kritsky et al pointed out that excited flavins, which can photocatalyze reactions leading to the accumulation of free energy in the products, were available in the earliest stage of evolution [105]. Recent genomic and molecular structural comparison studies on various photosynthetic microbes suggested that at least either PS I or PS II systems might have started separately and then merged into oxygen generating systems in cyanobacteria and plants by means of endosymbiosis [95,96].…”
Section: Origin and Evolution Of Photosynthesis: A New Hypothesismentioning
confidence: 99%